2009
DOI: 10.1111/j.1743-6109.2009.01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Sexually Related Personal Distress in Women with Low Sexual Desire

Abstract: Introduction Sexual distress is an important component of diagnostic criteria for sexual dysfunctions, but little is known about the factors associated with sexual distress in women with low sexual desire. Aim To investigate the correlates of sexual distress in women with self-reported low sexual desire. Methods The Prevalence of Female Sexual Problems Associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
104
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(121 citation statements)
references
References 17 publications
15
104
0
2
Order By: Relevance
“…In addition, our study confirmed earlier findings showing that relational satisfaction is relevant to the prediction of sexual distress due to desire and arousal impairments, but this was only significant for perceived partner-and interpersonal distress, 3,[15][16][17][18][19][20] Women have various reasons to engage in sex with their partner. 39 However, with the presence of a sexual impairment, the motivation to have sex is more likely to be influenced by interpersonal compared to intrapersonal reasons.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In addition, our study confirmed earlier findings showing that relational satisfaction is relevant to the prediction of sexual distress due to desire and arousal impairments, but this was only significant for perceived partner-and interpersonal distress, 3,[15][16][17][18][19][20] Women have various reasons to engage in sex with their partner. 39 However, with the presence of a sexual impairment, the motivation to have sex is more likely to be influenced by interpersonal compared to intrapersonal reasons.…”
Section: Discussionsupporting
confidence: 79%
“…3,15,17 This finding further underscores the importance of differentiating between general distress about sexuality and distress that is specifically due to a sexual impairment.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations